GAMBARAN PEMANFAATAN BILIK MENYUSUI DI KANTOR PEMERINTAHAN KABUPATEN HULU SUNGAI UTARA - Hidayati, Nurmila; Zulliati, Zulliati; Lestari, Yayuk Puji (LPPM Universitas Sari Mulia, 2024)
Background: Exclusive breastfeeding for babies is very important and given until the baby is 6 months old. Breast milk, which is produced naturally by the body, contains nutrients that are important for the growth and development of babies, such as vitamins, proteins, carbohydrates and fats. One of the obstacles experienced by breastfeeding mothers in exclusive breastfeeding is if the mother works as an employee in an agency, both government and private. Objective: To find out the Utilization of the ASI Booth in the North Hulu Sungai District Government Office. Methods: This type of research with quantitative research with a descriptive observational design. The sample is the Head of Service and breastfeeding mothers who work in 6 Offices of North Hulu Sungai Regency in January 2023 totaling 34 people, taken using a total sampling technique. Retrieval of data using observation sheets. Data were analyzed using univariate analysis. Results: Almost all of the respondents were aged 20-35 years, almost all of the respondents' children were >6 months old, almost all of the respondents' homes to the office were ≤5 Km and all of the respondents worked 8 hours per day. Utilization of ASI booths in 6 Offices of Hulu Sungai Utara District for mothers who use them and Leaders/Management, all respondents stated that the utilization of ASI booths was optimal (100%). Conclusion: Utilization of ASI booths in 6 Offices of Hulu Sungai Utara District for mothers who use them and for Leaders/Management, all respondents stated that the utilization of ASI booths was optimal. Keywords: Breastfeeding Room, Exclusive Breastfeeding